Kinematics Analysis and Simulation of A 5DOF Articulated Robotic Arm Applied to Heavy Products Harvesting - Ali Roshanianfard Roshanıanfard; Noboru Noguchı (Journal of Agricultural Sciences, 2018)
Robotics can play a significant role to increase efficiency and lighten the farmer’s load. Despite challenges in the agricultural robotic designs, robots are capable of performing various tasks and changing themselves accordingly, based on specific conditions. To address modern problems in the agricultural field, an agricultural robot is one of the key technologies. Although agricultural robotic is still in the development stage, robots have a bright future ahead. This paper proposes a new 5DOF articulated robotic arm design that would become a solution for heavy crop harvestings like pumpkin and cabbage. After the development stage, this robotic arm will be mounted on a robot tractor for real experimentation. The main design process of this robotic arm was conceived using 6 stages of Shigley design process. All components were designed, assembled and analyzed by using Solidworks 2014 in compliance with Japanese Industrial Standards (JIS) standards. The parts of the system that had dynamic nature were analyzed manually using standard mechanical formulas. Calculations of the workspace required joint torque, and coordination of mass center position was done by using standard machine design methods. Denavit-Hartenberg method was used to calculate forward and inverse kinematics. To resolve the torque reduction, components were designed using different materials and mass centers and comparing their performance. Results showed that total torque in Joints number 1, 2, 3, 4 and 5 were 6.15, 257.35, 103.4, 20.2 and 0.1 respectively with a rotational speed range of 15 ~ 60 rpm. Changes in the linkage material and servo motor location improved 29.7% ~ 47.7% and 29.7% ~ 68.9% of the total required torque for each joint. The maximum distance covered by the arm was 1421 mm from the and 2026 mm from the attachment point. According to the feedback received